(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article is devoted to the study of the analysis of theoretical aspects of national security and technologies for making political decisions. Analysis of political tasks and technology of interaction between the state and the Jogorku Kenesh of the Kyrgyz Republic, which made it possible, through the prism of manipulative, normative, structural-functional, and comparative approaches, to present models using the example of the Jogorku Kenesh as a multidimensional socio-political phenomenon, as well as an integrated interdisciplinary system of knowledge